Silicon Fertilizer Application Promotes Phytolith Accumulation in Rice Plants - Sun, Xing; Liu, Qin; Tang, Tongtong; Chen, Xiang; Luo, Xia (Frontiers in Plant Science, 2019)
In this study, a pot experiment was designed to elucidate the effect of varying dosages of silicon (Si) fertilizer application in Si-deficient and enriched paddy soils on rice phytolith and carbon (C) bio-sequestration within phytoliths (PhytOC). The maximum Si fertilizer dosage treatment (XG3) in the Si-deficit paddy soil resulted in an increase in the rice phytolith content by 100.77% in the stem, 29.46% in the sheath and 36.84% in the leaf compared to treatment without Si fertilizer treatment (CK). However, the maximum Si fertilizer dosage treatment (WG3) in the Si -enriched soil increased the rice phytolith content by only 32.83% in the stem, 27.01% in the sheath and 32.06% in the leaf. Overall, Si fertilizer application significantly (p < 0.05) increased the content of the rice phytoliths in the stem, leaf and sheath in both the Si-deficient and enriched paddy soils, and the statistical results showed a positive correlation between the amount of Si fertilizer applied and the rice phytolith content, with correlation coefficients of 0.998 (p < 0.01) in the Si-deficient soil and 0.952 (p < 0.05) in the Si-enriched soil. In addition, the existence of phytoliths in the stem, leaf, and sheath of rice and its content in the Si-enriched soil were markedly higher than that in the Si-deficient soil. Therefore, Si fertilizer application helped to improve the phytolith content of the rice plant.